2020
DOI: 10.1080/09540121.2020.1785998
|View full text |Cite
|
Sign up to set email alerts
|

Emotional health outcomes are influenced by sexual minority identity and HIV serostatus

Abstract: For people living with HIV (PLWH) and sexual minorities (SM), the intersection of identities can compound experiences like stigma and discrimination resulting in poor emotional health. We investigated the separate and interactive associations of HIV serostatus and sexual identity with emotional health. Our dataset included 371 participants. Emotional health was assessed by the NIH Toolbox emotion battery which yields negative affect, social satisfaction, and psychological well-being. Regressions were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
1
3
0
2
Order By: Relevance
“…Kamen et al [63] reported higher stigma levels in heterosexuals. This result is in line with some studies (e.g., [84] and can also be explained by a stigma accumulation in ethnic minority groups. Only one study by Rzeszutek et al [74] showed an interesting moderating role of relationship status for the association between life satisfaction and PTG.…”
Section: Summary Of Main Findingssupporting
confidence: 93%
“…Kamen et al [63] reported higher stigma levels in heterosexuals. This result is in line with some studies (e.g., [84] and can also be explained by a stigma accumulation in ethnic minority groups. Only one study by Rzeszutek et al [74] showed an interesting moderating role of relationship status for the association between life satisfaction and PTG.…”
Section: Summary Of Main Findingssupporting
confidence: 93%
“…Doric 2020 Serbia Cross-sectional HIV Stigma Scale Subjective well-being (Satisfaction with Life Scale and Positive and Negative Affect Scale) N = 90; M = 79, F = 11; Age mean = 41.64 HM = 42, HT = 41, B = 7 100% Caucasian 37.3% higher education; 33.9% stable relationship; 44.1% employed 7.88 years since diagnosis/ treatment No significant covariates 59. Nguyen et al 2020 USA Cross-sectional Lesbian and Gay Identity Scale Affective well-being (NIHTB-EB Battery) N = 371; M = 332, F = 39; Age mean = 52.10 HM = 294, HT = 50, B = 27 62.1% Caucasian, 23.2% Latino, 14.7% African 23% higher education Mean CD4: 644.2; 17.3% detectable viral load Sexual orientation (sexual minority status associated with higher well-being and lower stigma) 60. Parcesepe et al 2020 Tanzania Cross-sectional HIV/AIDS Stigma Instrument Quality of life (overall QL; HIV/AIDS Targeted Quality of Life instrument) N = 912; M = 336, F = 576; Age mean = 31.10 n/a 100% African 58.1% stable relationship; 61.1% employed Mean CD4: 210.2 Gender (lower QL and higher stigma in men) and relationship (being in a stable relationship associated with lower stigma and higher quality of life) 61.…”
Section: Resultsmentioning
confidence: 99%
“…lesbian, gay, and bisexual) experienced higher stigma and declared substantially lower quality of life compared to heterosexual PLWH. Only Nguyen et al ( 2020 ) found higher well-being among PLWH representing sexual and gender minorities compared to heterosexual PLWH, although there was no significant difference in the stigma level between these two groups. Furthermore, in six out of nine eligible studies, African and/or African American PLWH reported higher stigmatization and lower well-being compared to PLWH of Caucasian ethnicity, although Heckman et al ( 2002 ) and Earnshaw et al ( 2013 ) observed the reverse and Kang, Rapkin, Remien, Mellins, and Oh ( 2005 ) found the lowest well-being and the highest stigma among Asian PLWH.…”
Section: Summary Of Main Findings and Discussionmentioning
confidence: 95%
“…The current findings generally support prior research indicating that PWH have more problematic emotional health than their peers within the general population. 4 , 35 , 36 The fact that the PWH evidenced much more difficulty on some NIHTB-EB scales (eg, those reflecting problems and unhappiness with their social relationships) than others (eg, reflecting anger and hostility) speaks to the apparent specificity of individual scales and the potential clinical value of measuring a broad range of emotional health factors. As a further example of specificity of the NIHTB-EB components, relationship status among PWH was strongly related to Social Satisfaction, but was essentially unrelated to Negative Affect or Psychological Well Being.…”
Section: Discussionmentioning
confidence: 99%